MAKNA DAN KRITERIA DISKRESI KEPUTUSAN DAN/ATAU TINDAKAN PEJABAT PUBLIK DALAM MEWUJUDKAN TATA PEMERINTAHAN YANG BAIK - Susilo, Agus Budi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
In order to do the legal action, public officials often execute out of written law, this condition is a logic consequence, that the acts and others written laws are left behind in anticipating the development of the era, the change of values, and increasing need of human life along with the progress that they have achieved in science and technology. Therefore, to make legality principle on operational stage can be done as good as it could, so the development instrument of the discretion is needed, ironically, not the rare things, the use of discretion sometimes misuse by public officials, pretending bases on public need and legal certainty in fact they abandon civil rights, either individually, in group or even civil corporate body. To anticipate it all, another draft is required to control the discretion of public policy and/or act of public officials, and that draft is good governance, which usually assume as good governance system. By understanding main principle from good governance itself, it’s hoped that the discretion of public policy and/or act of public officials can be applied together with code of conduct in law (rechtmatigheid van regering).Keywords : Discretion, Public Officials, Good Governance